Effects of Mixture of Pharmaceuticals on Early Life Stages of Tench (Tinca tinca). (20th March 2014) - Stancova, Vlasta; Plhalova, Lucie; Bartoskova, Marta; Zivna, Dana; Prokes, Miroslav; Marsalek, Petr; Blahova, Jana; Skoric, Misa; Svobodova, Zdenka
Abstract : Ubiquitous occurrence of pharmaceuticals in aquatic environment results in concern about potential adverse the effects on nontarget organisms. In water, drugs are present in complex mixtures, in which complicated interactions affect toxicity of single components. The purpose of this study was to examine effect of 35-day-long exposure to mixture of ibuprofen, diclofenac, and carbamazepine on the mortality, growth, early ontogeny, and histopathological changes in tench ( Tinca tinca ). Early life stage toxicity test was carried out using a modified protocol according to OECD guideline 210. Exposure to mixture of pharmaceuticals at concentration of 60  μ g·L −1 for each substance was associated with significant increase in mortality, as well as significant increase in growth and elevated incidence of malformations. Any of the tested concentrations resulted in histopathological changes of liver, kidney, skin, or gill. After fourteen days of exposure there was short-term delay of development related to increased concentrations of pharmaceuticals in the mixture (2, 20, and 60  μ g·L −1 ). Environmentally relevant concentrations (0.02; and 0.2  μ g·L −1 ) used in this experiment did not result in toxic impairment of tench.